The new New Deal fracas: Did Roosevelt's anticompetitive legislation slow the recovery from the Great Depression? - Dimitri B. Papadimitriou; Greg Hannsgen (Levy Economics Institute of Bard College, 2009)
A wave of revisionist work claims that anticompetitive New Deal legislation such as the National Industrial Recovery Act (NIRA) and the National Labor Relations Act (NLRA) greatly slowed the recovery from the Depression; in this new public policy brief, President Dimitri B. Papadimitriou and Research Scholar Greg Hannsgen review these claims in light of current policy debates and cast into doubt the argument that NIRA and NLRA significantly prolonged or worsened the Depression. Moreover, Social Security, federal deposit insurance, and other New Deal programs helped usher in an era of relative prosperity following World War II. When it comes to combating the current recession and employment slump, it is the successful experience with relief and public works, and not the repercussions of pro-union and regulatory legislation, that offer the most relevant and helpful lessons.
Keywords: 330